Criminal systems - a global threat for the nation's security - Botos, Ilie ([s.n.] Antigua GuatemalaGT, 2004)
Looks at criminality, organized crime, corruption and terrorism. Examines Romania's national strategy for the prevention of and combat of criminality. Highlights the role and duties of the Romanian Public Ministry in acknowledging, preventing and limiting the criminal phenomenon. Looks at bilateral and international cooperation.